Black monologues in schools: Black Theater in teacher education (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In this section, we will address the manifestation of black epistemologies in the pedagogical journey of the Solos Negros nas Escolas project (Black Monologues In Schools) in the year 2023, an initiative that aims to value and share the foundations of Law 10.639/03 in Theater Pedagogy. The procedures adopted in this initiative aim at the active participation of students, promoting student leadership in the collective construction of knowledge, in tune with Afro-Brazilian civilizing values. In this way, Solos Negros promotes teacher training that goes beyond the mere reproduction of content, encouraging reflection, creativity and commitment to anti-racist education.
Keywords: black theater; antiracist education; teacher training